Twenty elite upland rice breeding lines exceeding NERICA 4 in yield by more than 20% identified in Cote d'Ivoire - CGIAR Research Program on Rice (2021)
Yield trials were conducted on-station in Cote d'Ivoire in 2019 and 20 lines were identified that exceeded the yield of NERICA 4, the best check by more than 20%. The lines were advanced for testing in multi-location trials with NARS partners.